Perovskite solar cell

By using thiol-based small molecule modification layer in perovskite solar cells to regulate the Fermi energy level and oxidation potential of metal electrodes, the problems of low interface efficiency, poor stability and high cost in perovskite solar cells are solved, and an efficient, stable and economical perovskite solar cell is achieved.

CN119521927APending Publication Date: 2025-02-25TAN KAH KEE INNOVATION LAB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311061190.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In perovskite solar cells, the interface efficiency between the metal electrode and the charge transport layer is low, resulting in low efficiency; the metal electrode is easy to react with the perovskite components, resulting in stability problems; the precious metal electrode is high in cost and the non-precious metal electrode has poor stability.

Method used

Small thiol molecules (such as phenyl mercaptan and alkyl mercaptan) are used as modification layers to regulate the Fermi energy level and oxidation potential of metal electrodes, and improve the efficiency and stability of perovskite solar cells.

Benefits of technology

By regulating the Fermi energy level and oxidation potential of metal electrodes, the photoelectric conversion efficiency and stability of perovskite solar cells are improved and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119521927A_ABST
    Figure CN119521927A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite solar cell which comprises a metal electrode layer, a modification layer, a first carrier transport layer, a perovskite layer, a second carrier transport layer and a conductive substrate, and the material of the modification layer is selected from a substituted or unsubstituted phenyl thiol compound, a substituted or unsubstituted alkyl thiol compound and a combination thereof. Phenyl mercaptan or alkyl mercaptan is used as the modification layer in the perovskite solar cell, so that the Fermi level and oxidation potential of a metal electrode (including various metals, gold, silver and copper which are commonly used for electrode materials) can be regulated and controlled, and the metal electrode can be applied to various perovskite solar cells; meanwhile, the preparation cost of the device is reduced, the stability of the device is improved, and the application prospect and advantages are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of solar cells, and in particular to the field of perovskite solar cells. Background Art

[0002] Perovskite solar cells have become a promising new photovoltaic device due to their low manufacturing cost brought by the solution deposition process. However, in the process of promoting the commercialization of perovskite solar cells, three key issues remain to be resolved: improving the uniformity of large-area materials, improving device stability, and further reducing device costs. Perovskite photovoltaic devices are thin-film devices composed of a perovskite photoactive layer, a charge transport layer, and an electrode layer. The perovskite layer absorbs light and generates free photogenerated electron-hole pairs. The charge transport layer extracts electrons and holes from both sides of the perovskite film, and the electrode layer further extracts electrons and holes from the transport layer and forms a loop with the external circuit.

[0003] At present, the electrode material commonly used in perovskite photovoltaic devices is metal film. Metal electrodes have the following problems: (1) The charge extraction efficiency at the interface between the metal electrode and the charge transport layer greatly affects the efficiency of the perovskite solar device, and the matching degree between the metal Fermi level and the (hole / electron) transport layer (valence band / conduction band) energy level affects the device efficiency; (2) Metal materials tend to react with the halogen ions in the perovskite component, resulting in metal corrosion and perovskite degradation, affecting the stability of the perovskite solar device; (3) The use of precious metal electrodes (such as gold and silver) increases the overall preparation cost of the device, which is not conducive to the large-scale preparation of perovskite photovoltaic devices; if the precious metal electrode is replaced with a non-precious metal material (such as copper and aluminum), the stability problem faced by the interface will be more prominent. In order to obtain a perovskite solar cell with both high efficiency and high stability and reduce its large-scale preparation cost, the optimization of the metal electrode is of great research significance. In the prior art, interface modification methods are commonly used to improve the stability of the metal electrode system. For example, interface coating (Nat. Commun. 2019, 10, 1161), interface small molecule modification (Sci. Adv. 2020, 6, 1580), interface graphene modification (Nat. Energy 2022, 7, 520-527), etc., try to replace the precious metal electrodes commonly used in perovskite devices with copper electrodes. Copper has a bulk conductivity similar to that of gold and silver, and has good application prospects in perovskite devices. However, the current problems and solutions faced by copper electrodes are: (1) The Fermi level of the copper electrode (about -4.85 eV) is far from the valence band energy level of the hole transport layer. In order to achieve efficient interface transmission, it is necessary to regulate the Fermi level of the lower surface of the copper electrode; (2) Copper itself is easily oxidized and corroded, which affects the stability of the device. Therefore, it is necessary to increase the oxidation potential of copper to achieve antioxidant properties. In order to realize the large-scale application of copper electrodes in stable and efficient perovskite solar devices, it is necessary to simultaneously regulate the Fermi level and oxidation potential of the copper electrodes, and key technologies still need to be developed. Summary of the invention

[0004] The present invention uses thiol small molecules (including substituted or unsubstituted phenylthiol compounds, substituted or unsubstituted alkylthiol compounds and combinations thereof) to modify the interface between the metal electrode and the transport layer in the perovskite solar device, thereby improving the efficiency and overall stability of the device.

[0005] Therefore, the present application provides a perovskite solar cell, comprising:

[0006] Metal electrode layer,

[0007] Modification layer,

[0008] The first carrier transport layer,

[0009] Perovskite layer,

[0010] a second carrier transport layer, and

[0011] Conductive substrate,

[0012] Wherein, the constituent material of the modification layer is selected from substituted or unsubstituted phenylthiol compounds, substituted or unsubstituted alkylthiol compounds and combinations thereof.

[0013] In one embodiment, the substituted or unsubstituted phenylthiol compound has a structural formula of Formula I,

[0014]

[0015] Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

[0016] In one embodiment, the substituted or unsubstituted phenylthiol compound has the structural formula of Formula I-1,

[0017]

[0018] Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

[0019] In one embodiment, R 1 Independently selected from H, F, methyl, trifluoromethyl, -SO2CF3.

[0020] In one embodiment, the substituted or unsubstituted alkylthiol compound has a structural formula II,

[0021]

[0022] Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl;

[0023] R 3 and R 4 is independently selected at each occurrence from H, halogen, C1-C6 alkyl and C1-C6 haloalkyl;

[0024] n is 1-5.

[0025] In one embodiment, the substituted or unsubstituted alkylthiol compound has the structural formula of Formula II-1,

[0026]

[0027] Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl;

[0028] n is 1-5.

[0029] In one embodiment, R 2 Independently selected from H, F, methyl, trifluoromethyl, -SO2CF3.

[0030] In one embodiment, the first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer.

[0031] In one embodiment, the first carrier transport layer is an electron transport layer, and the second carrier transport layer is a hole transport layer.

[0032] In one embodiment, the hole transport layer comprises a p-type inorganic or organic semiconductor material, preferably selected from NiO x , CuI, CuSCN, spiro-OMeTAD, P3HT, PTAA and combinations thereof.

[0033] In one embodiment, the constituent material of the electron transport layer includes an n-type inorganic or organic semiconductor material, preferably selected from PCBM, ZnTiO3, TiO2, SnO2, ZnO, ZnO-ZnS and combinations thereof.

[0034] In one embodiment, the thickness of the electron transport layer is 10-120 nm; the thickness of the hole transport layer is 50-300 nm.

[0035] In one embodiment, the metal electrode layer is selected from gold, silver, copper, aluminum and alloys thereof.

[0036] In one embodiment, the perovskite layer comprises AMX3, wherein A is selected from C4H 11 N + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb+ and combinations thereof; M is selected from Pb 2+ and Sn 2+ and combinations thereof; X is selected from halogen ions and quasi-halogen ions and combinations thereof.

[0037] In one embodiment, the thickness of the perovskite layer is 100-800 nm.

[0038] In one embodiment, the thickness of the modified layer is 2-5 nm.

[0039] The present application uses phenylthiol or alkylthiol as a modification layer in perovskite solar cells to regulate the Fermi level and oxidation potential of metal electrodes (including a variety of metals commonly used as electrode materials, gold, silver, and copper), so that they can be applied to a variety of perovskite solar cells. At the same time, it is committed to reducing the preparation cost of the device and improving the stability of the device, and has great application prospects and advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic structural diagram of a perovskite solar cell is shown.

[0041] Figure 2-1 The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the copper Fermi level and the copper Fermi level after modification with 4-substituted phenylthiol (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively) is shown.

[0042] Figure 2-2 The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the gold Fermi level and the gold Fermi level after modification with 4-substituted phenylthiol (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively) is shown.

[0043] Figure 2-3 The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the gold Fermi level and the silver Fermi level modified by 4-substituted phenylthiol (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively) is shown.

[0044] Figure 3-1 The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the copper Fermi level and the copper Fermi level after modification with 4-substituted butyl mercaptan (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively) is shown.

[0045] Figure 3-2The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the gold Fermi level and the gold Fermi level after modification with 4-substituted butyl mercaptan (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively) is shown.

[0046] Figure 3-3 The comparison of the valence band energy levels of hole transport materials, the conduction band energy levels of electron transport materials, the silver Fermi level and the silver Fermi level modified by 4-substituted butyl mercaptan (the substituents R are -SO2CF3, -CF3, -F, -H, -CH3, respectively).

[0047] Figure 4-1 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Current density-voltage curve of an upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and a copper electrode as the back electrode (the experimental group uses 4-trifluoromethylphenylthiol as the modification layer, while the control group does not contain this modification layer).

[0048] Figure 4-2 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and copper electrode as back electrode (the experimental group uses 4-trifluoromethylphenylthiol as the modification layer, the control group does not contain the modification layer, and the test environment is 65°C, 65% relative humidity).

[0049] Figure 4-3 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and copper electrode as back electrode (the experimental group uses 4-trifluoromethylphenylthiol as the modification layer, the control group does not contain the modification layer, the test environment is 60℃, nitrogen environment).

[0050] Figure 4-4 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 PbI3 is the perovskite layer, NiO x The current density-voltage curve of an upright solar cell with a hole transport layer and a copper electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain this modification layer).

[0051] Figure 4-5 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs0.05 PbI3 is the perovskite layer, NiO x The cell stability test curve of an upright solar cell with a hole transport layer and a copper electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain the modification layer).

[0052] Figure 4-6 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Current density-voltage curve of an upright solar cell with PbI3 as the perovskite layer, P3HT as the hole transport layer, and a gold electrode as the back electrode (the experimental group uses 4-fluorophenylthiol as the modification layer, while the control group does not contain this modification layer).

[0053] Figure 4-7 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The cell stability test curve of the upright solar cell with PbI3 as the perovskite layer, P3HT as the hole transport layer, and a gold electrode as the back electrode (the experimental group uses 4-fluorophenylthiol as the modification layer, and the control group does not contain this modification layer).

[0054] Figure 4-8 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Current density-voltage curve of an upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and a silver electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, while the control group does not contain this modification layer).

[0055] Figure 4-9 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and silver electrode as back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain this modification layer).

[0056] Figure 4-10 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Current density-voltage curve of an upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and a copper electrode as the back electrode (the experimental group uses 5,5,5-trifluoropentane-1-thiol as the modification layer, and the control group does not contain this modification layer).

[0057] Figure 4-11It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and copper electrode as back electrode (the experimental group uses 5,5,5-trifluoropentane-1-thiol as the modification layer, and the control group does not contain this modification layer).

[0058] Figure 4-12 The hole transport layer is PTAA, and the FA 0.95 Cs 0.05 Current density-voltage curve of inverted solar cell with PbI3 as perovskite layer, PCBM as electron transport layer and gold electrode as back electrode (the experimental group uses 4-methylphenylthiol as the modification layer, while the control group does not contain this modification layer).

[0059] Figure 4-13 The hole transport layer is PTAA, and the FA 0.95 Cs 0.05 Stability test curve of inverted solar cells with PbI3 as perovskite layer, PCBM as electron transport layer and gold electrode as back electrode (the experimental group uses 4-methylphenylthiol as the modification layer, and the control group does not contain this modification layer). DETAILED DESCRIPTION

[0060] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.

[0061] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.

[0062] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0063] like Figure 1 As shown, the present application provides a perovskite solar cell, comprising:

[0064] Metal electrode layer 1,

[0065] Modification layer 2,

[0066] The first carrier transport layer 3,

[0067] Perovskite layer 4,

[0068] The second carrier transport layer 5,

[0069] Conductive substrate 6,

[0070] The constituent material of the modification layer 2 is selected from substituted or unsubstituted phenylthiol compounds, substituted or unsubstituted alkylthiol compounds and combinations thereof.

[0071] The solar cell of the present application can be an upright solar cell (i.e., nip type) or an inverted solar cell (i.e., pin type), that is, the positions of the electron transport layer and the hole transport layer can be interchanged. In an upright solar cell, a conductive substrate 6, a second carrier transport layer 5 (electron transport layer), a perovskite layer 4, a first carrier transport layer 3 (hole transport layer), a modified layer 2, and a metal electrode layer 1 can be included in sequence. In an inverted solar cell, a conductive substrate 6, a second carrier transport layer 5 (hole transport layer), a perovskite layer 4, a first carrier transport layer 3 (electron transport layer), a modified layer 2, and a metal electrode layer 1 can be included in sequence.

[0072] The perovskite solar cell of the present application includes a conductive substrate 6, and various conductive substrates commonly used in the art can be used, such as ITO (Indium Tin Oxide) or FTO (F-doped Tin Oxide) conductive glass, etc.

[0073] The perovskite solar cell of the present application comprises a perovskite layer 4. According to the present application, the perovskite layer comprises AMX3, wherein A is selected from C4H 11 N + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + and combinations thereof; M is selected from Pb 2+ and Sn 2+ and combinations thereof. Halogen ions include chloride ions, bromide ions, and iodide ions. Quasi-halogen ions may include thiocyanate ions, cyanide ions, and the like.

[0074] The method for forming the perovskite layer can be a method known in the art, for example, the perovskite precursor solution can be coated by one or more processes such as spin coating, blade coating, Czochralski coating, slit coating, spray coating, etc., and then the perovskite layer can be formed through a curing reaction. In one embodiment, the thickness of the perovskite layer 4 can be 100-800nm.

[0075] In one embodiment, the electron transport layer may include an n-type inorganic or organic semiconductor material, preferably selected from PCBM, ZnTiO3, TiO2, SnO2, ZnO, ZnO-ZnS and combinations thereof. In one embodiment, the thickness of the electron transport layer may be 10-120 nm.

[0076] In one embodiment, the hole transport layer may include a p-type inorganic or organic semiconductor material, preferably selected from NiO x , CuI, CuSCN, spiro-OMeTAD (2,2′,7,7′-tetrakis(N,N-di-p-methoxyphenylamine))9,9′-spirobifluorene), P3HT (poly 3-hexylthiophene), PTAA (poly [bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) and combinations thereof. In one embodiment, the thickness of the hole transport layer is 50-300 nm.

[0077] In one embodiment, the metal electrode layer 1 may include various metal electrodes used in the art, preferably selected from gold, silver, copper or carbon, ITO and a combination thereof. In one embodiment, the thickness of the metal electrode is 10-100 nm.

[0078] In the solar cell of the present application, a modification layer 2 is also provided between the metal electrode layer 1 and the first carrier transport layer 3, which is used to regulate the Fermi level and oxidation potential of the metal electrode (including a variety of metals commonly used in electrode materials, gold, silver, and copper), so that it can be applied to a variety of perovskite solar cells, while being committed to reducing the preparation cost of the device and improving the stability of the device. The modification layer 2 is generally arranged in contact with the metal electrode layer 1 and is arranged close to the first carrier transport layer 3. As described above, in an upright solar cell (i.e., nip type), the first carrier transport layer 3 can be a hole transport layer. In an inverted solar cell (i.e., pin type), the first carrier transport layer 3 can be an electron transport layer.

[0079] In one embodiment, the constituent material of the modification layer 2 may be selected from substituted or unsubstituted phenylthiol compounds, substituted or unsubstituted alkylthiol compounds, and combinations thereof.

[0080] In one embodiment, the substituted or unsubstituted phenylthiol compound has a structural formula of Formula I,

[0081]

[0082] Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

[0083] In one embodiment, the substituted or unsubstituted phenylthiol compound has the structural formula of Formula I-1,

[0084]

[0085] Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

[0086] In one embodiment, R 1 Independently selected from H, F, methyl, trifluoromethyl, -SO2CF3.

[0087] In one embodiment, the substituted or unsubstituted alkylthiol compound has a structural formula II,

[0088]

[0089] Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl;

[0090] R 3 and R 4 is independently selected at each occurrence from H, halogen, C1-C6 alkyl and C1-C6 haloalkyl;

[0091] n is 1-5.

[0092] In one embodiment, the substituted or unsubstituted alkylthiol compound has the structural formula of Formula II-1,

[0093]

[0094] Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl;

[0095] n is 1-5.

[0096] In one embodiment, R 2 In one embodiment, n can be 2, 3 or 4.

[0097] In one embodiment, examples of phenylthiols and alkylthiols that can be used in the present application include, but are not limited to, 4-trifluoromethylphenylthiol, 4-fluorophenylthiol, 4-methylphenylthiol, phenylthiol, 4-trifluoromethylsulfonylphenylthiol, 5,5,5-trifluoropentane-1-thiol, 4-fluorobutane-1-thiol, pentane-1-thiol, 4-((trifluoromethyl)sulfonyl)butane-1-thiol, etc. These phenylthiols and alkylthiols can be commercially available or synthesized by conventional methods known in the art.

[0098] The inventors of the present application have found that the Fermi level and oxidation potential of the metal surface can be regulated by regulating the substituents on phenylthiol and alkylthiol. Thiol compounds with different substituents can give different Fermi levels and oxidation potentials to the surfaces under different metal electrodes, thereby matching transport layers with different energy levels (such as Figure 2-1 to Figure 3-3 shown).

[0099] Figure 2-1 In the figure, different hole transport materials such as NiO are shown. x , PTAA, spiro-OMeTAD( Figure 2-1 spiro), P3HT, PCBM valence band energy level, and the modified layer is respectively 4-substituted phenylthiol (substituent R 1 The Fermi level and oxidation potential of the copper electrode under the surface when the Figure 2-1 where -SO2CF3, -CF3, -F, -H, -CH3 represent the modification layer composed of thiol compounds whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3, respectively), and the Fermi level and oxidation potential of the copper electrode itself without the modification layer ( Figure 2-1 Cu is used in the above formula. Figure 2-2 Different hole transport materials such as NiO are shown x , PTAA, spiro-OMeTAD( Figure 2-2 spiro), P3HT, PCBM valence band energy level, and the modified layer is respectively 4-substituted phenylthiol (substituent R 1 The Fermi level and oxidation potential of the lower surface of the gold electrode ( Figure 2-2 In which -SO2CF3, -CF3, -F, -H, -CH3 represent the modification layer composed of thiol compounds whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3 respectively), and the Fermi level and oxidation potential of the gold electrode itself without the modification layer ( Figure 2-2 (denoted by Au in the figure). Figure 2-3 Different hole transport materials such as NiO are shownx , PTAA, spiro-OMeTAD( Figure 2-3 spiro), P3HT, PCBM valence band energy level, and the modified layer is respectively 4-substituted phenylthiol (substituent R 1 The Fermi level and oxidation potential of the lower surface of the silver electrode ( Figure 2-3 wherein -SO2CF3, -CF3, -F, -H, -CH3 represent a modification layer composed of a thiol compound whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3, respectively), and the Fermi level and oxidation potential of the silver electrode itself without the modification layer ( Figure 2-3 (denoted by Ag in the figure).

[0100] Figure 3-1 In the figure, different hole transport materials such as NiO are shown. x , PTAA, spiro-OMeTAD( Figure 3-1 spiro), P3HT, PCBM valence band energy level, and the modified layer is a substituted alkylthiol of formula II-1 (n is 2, the substituent R 2 The Fermi level and oxidation potential of the copper electrode under the surface when the Figure 3-1 where -SO2CF3, -CF3, -F, -H, -CH3 represent the modification layer composed of thiol compounds whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3, respectively), and the Fermi level and oxidation potential of the copper electrode itself without the modification layer ( Figure 3-1 Cu is used in the above formula. Figure 3-2 In the figure, different hole transport materials such as NiO are shown. x , PTAA, spiro-OMeTAD( Figure 3-2 spiro), P3HT, PCBM valence band energy level, and the modified layer is a substituted alkylthiol of formula II-1 (n is 2, the substituent R 2 The Fermi level and oxidation potential of the lower surface of the gold electrode ( Figure 3-2 In which -SO2CF3, -CF3, -F, -H, -CH3 represent the modification layer composed of thiol compounds whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3 respectively), and the Fermi level and oxidation potential of the gold electrode itself without the modification layer ( Figure 3-2 (denoted by Au in the figure). Figure 3-3 In the figure, different hole transport materials such as NiO are shown. x, PTAA, spiro-OMeTAD( Figure 3-3 spiro), P3HT, PCBM valence band energy level, and the modified layer is a substituted alkylthiol of formula II-1 (n is 2, the substituent R 2 The Fermi level and oxidation potential of the lower surface of the silver electrode ( Figure 3-1 wherein -SO2CF3, -CF3, -F, -H, -CH3 represent a modification layer composed of a thiol compound whose substituent R is -SO2CF3, -CF3, -F, -H, -CH3, respectively), and the Fermi level and oxidation potential of the silver electrode itself without the modification layer ( Figure 3-3 (denoted by Ag in the figure).

[0101] Taking spiro-OMeTAD, the most common hole transport layer, as an example, the valence band energy level of spiro-OMeTAD is located at -5.08 eV. 1 The Fermi levels of the copper electrodes modified with -SO2CF3 and -CF3 are respectively -5.10eV and -5.02eV, which are close to the valence band of spiro-OMeTAD, and help to achieve efficient hole transport. At the same time, the oxidation potential of the modified copper electrode is below the valence band of spiro-OMeTAD, which can effectively resist the corrosion of photogenerated holes (positive charges).

[0102] Therefore, a suitable modification layer material can be selected according to the material of the first carrier transport layer (hole transport layer or electron transport layer) used, for example, by regulating the substituents on phenylthiol and alkylthiol, the Fermi level and oxidation potential of the metal surface can be regulated to match the selected first carrier transport layer (hole transport layer or electron transport layer). Vice versa, the material of the appropriate first carrier transport layer (hole transport layer or electron transport layer) can be selected according to the modification layer material used. In one embodiment, the thickness of the modification layer can be 2-5 nm.

[0103] Example 1

[0104] With ZnTiO3 as electron transport layer, FA 0.95 Cs 0.05 Preparation, efficiency and stability testing of inverted perovskite solar cells with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer, 4-trifluoromethylphenylthiol as modification layer and copper electrode as back electrode.

[0105] Preparation method: Ultrasonic clean the FTO transparent conductive glass with detergent, water, ethanol, and acetone in sequence, and treat it in a UV ozone cleaner for 30 minutes. Place the cleaned conductive glass substrate on a hot plate and apply the electron transport layer by spraying. After the substrate temperature rises to 450°C, spray the pre-configured precursor solution (10mM diisopropyl diacetylacetonate titanium and 10mM zinc acetate in ethanol) for 3 circles at a flow rate of 2mL / min. After spraying, place the substrate on a 450°C hot plate for 30 minutes and take it out after it cools naturally. Dilute the mesoporous titanium dioxide colloid with isopropanol at a volume ratio of 1:7, and spin coat it on the ZnTiO3 surface at 5000 rpm to form a mesoporous layer. Prepare the perovskite precursor solution: 0.03mmol cesium iodide, 0.97mmol formamidine iodide, 1.00mmol lead iodide, 20mg MACl dissolved in 600μL N,N'-dimethylformamide and 93μL N-methylpyrrolidone, ultrasonically dissolve it fully and filter to obtain a clear solution. Spin the precursor solution on the surface of the electron transport layer at 4000 rpm for 30 seconds, and treat it with ethyl acetate anti-solvent 12 seconds before the end of spin coating. The spin-coated perovskite film is placed on a 150℃ hot stage for annealing for 15 minutes. The coating of the Spiro-OMeTAD hole layer was performed by using a mixed solution of 73.2 mg / mL spiro-OMeTAD, 8.6 μL / mL bis(trifluoromethane)sulfonyl imide lithium salt in acetonitrile solution (520 mg / mL), and 14.4 μL / mL 4-tert-butylpyridine, which was dynamically spin-coated on the surface of the perovskite layer at 5000 rpm. The coating of the modification layer was performed by using an isopropanol solution of 4-trifluoromethylphenylthiol (concentration of 5 mg / mL) and spin-coated on the hole transport layer film at 3000 rpm. Finally, an electron beam evaporator was used at 6.0×10 -8 150nm copper electrode was deposited under vacuum (evaporation rate ).

[0106] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-1 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The current density-voltage curve of the upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and copper electrode as the back electrode (the experimental group uses 4-trifluoromethylphenylthiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 23.92 mA cm -2, the open circuit voltage is 1.086V, the fill factor is 72.42%, the photoelectric conversion efficiency is 18.81%, and the hysteresis coefficient is 6.2%. The reverse sweep short-circuit current of the experimental group is 24.62mA cm -2 , the open circuit voltage is 1.165V, the fill factor is 80.91%, the photoelectric conversion efficiency is 23.20%, and the hysteresis coefficient is 4.7%.

[0107] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed in two environments after packaging (65°C, 65% relative humidity) and (60°C, nitrogen environment) was tracked at different times. Figure 4-2 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and copper electrode as back electrode (the experimental group uses 4-trifluoromethylphenylthiol as the modification layer, the control group does not contain the modification layer, and the test environment is 65°C, 65% relative humidity). Figure 4-3 The efficiency changes of the devices of the same control group and experimental group at 60°C in a nitrogen environment are shown.

[0108] Example 2

[0109] With ZnTiO3 as electron transport layer, FA 0.95 Cs 0.05 PbI3 is the perovskite layer, NiO x Preparation, efficiency and stability testing of inverted perovskite solar cells with a hole transport layer, 4-trifluoromethylsulfonylphenylthiol as the modification layer and a copper electrode as the back electrode.

[0110] Preparation method: The cleaning of the conductive glass, the preparation of the electron transport layer and the perovskite layer are the same as in Example 1. Preparation of the hole transport layer: Synthesized oily NiO nanoparticles are used, dispersed in chlorobenzene at a concentration of 10 mg / mL, and ultrasonicated for 30 minutes to obtain a uniformly dispersed NiO dispersion. Dynamically spin-coated on the perovskite film at a speed of 3000 rpm. The coating of the modification layer uses an isopropanol solution of 4-trifluoromethylsulfonylphenylthiol (concentration of 5 mg / mL) and spin-coated on the hole transport layer film at a speed of 3000 rpm. The copper electrode preparation scheme is the same as in Example 1.

[0111] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-4 It shows that ZnTiO3 is used as the electron transport layer, FA0.95 Cs 0.05 PbI3 is the perovskite layer, NiO x The current density-voltage curve of the upright solar cell with a hole transport layer and a copper electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 23.79 mA cm -2 , the open circuit voltage is 1.057V, the fill factor is 69.14%, the photoelectric conversion efficiency is 17.38%, and the hysteresis coefficient is 5.8%. The reverse sweep short-circuit current of the experimental group is 24.42mA cm -2 , the open circuit voltage is 1.156V, the fill factor is 77.71%, the photoelectric conversion efficiency is 21.93%, and the hysteresis coefficient is 3.6%.

[0112] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed at 65°C and 65% relative humidity after packaging was tracked at different times. Figure 4-5 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 PbI3 is the perovskite layer, NiO x The cell stability test curve of an upright solar cell with a hole transport layer and a copper electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain the modification layer).

[0113] Example 3

[0114] With ZnTiO3 as electron transport layer, FA 0.95 Cs 0.05 Preparation, efficiency and stability testing of inverted perovskite solar cells with PbI3 as the perovskite layer, P3HT as the hole transport layer, 4-fluorophenylthiol as the modification layer and gold electrode as the back electrode.

[0115] Preparation method: The cleaning of the conductive glass, the preparation of the electron transport layer, and the perovskite layer were the same as in Example 1. The coating method of the hole transport layer was as follows: P3HT was dissolved in chlorobenzene at a concentration of 10 mg / mL and was dynamically spin-coated on the perovskite film at a speed of 3000 rpm. The coating of the modification layer was performed using an isopropanol solution of 4-fluorophenylthiol (concentration of 5 mg / mL) and was spin-coated on the hole transport layer film at a speed of 3000 rpm. Finally, an electron beam evaporator was used at 6.0×10 -8 100nm gold electrode was deposited under vacuum (evaporation rate ).

[0116] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-6 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The current density-voltage curve of the upright solar cell with PbI3 as the perovskite layer, P3HT as the hole transport layer, and gold electrode as the back electrode (the experimental group uses 4-fluorophenylthiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 24.01mA cm -2 , the open circuit voltage is 1.056V, the fill factor is 72.46%, the photoelectric conversion efficiency is 18.37%, and the hysteresis coefficient is 4.3%. The reverse sweep short circuit current of the experimental group is 24.61mAcm -2 , the open circuit voltage is 1.130V, the fill factor is 77.28%, the photoelectric conversion efficiency is 21.49%, and the hysteresis coefficient is 5.0%.

[0117] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed at 65°C and 65% relative humidity after packaging was tracked at different times. Figure 4-7 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The cell stability test curve of the upright solar cell with PbI3 as the perovskite layer, P3HT as the hole transport layer, and a gold electrode as the back electrode (the experimental group uses 4-fluorophenylthiol as the modification layer, and the control group does not contain this modification layer).

[0118] Example 4

[0119] With ZnTiO3 as electron transport layer, FA 0.95 Cs 0.05 Preparation, efficiency and stability testing of inverted perovskite solar cells with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer, 4-trifluoromethylsulfonylphenylthiol as modification layer and silver electrode as back electrode.

[0120] Preparation method: Cleaning of conductive glass, preparation of electron transport layer, perovskite layer, hole transport layer and modification layer are the same as in Example 1. Finally, electron beam evaporator was used at 4.0×10 -8 100nm silver electrode was deposited under vacuum (evaporation rate ).

[0121] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-8 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The current density-voltage curve of the upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and silver electrode as the back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 23.71mA cm -2 , the open circuit voltage is 1.095V, the fill factor is 74.22%, the photoelectric conversion efficiency is 19.28%, and the hysteresis coefficient is 5.5%. The reverse sweep short-circuit current of the experimental group is 24.50mA cm -2 , the open circuit voltage is 1.165V, the fill factor is 76.34%, the photoelectric conversion efficiency is 21.79%, and the hysteresis coefficient is 4.1%. Figure 4-7 shown.

[0122] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed at 65°C and 65% relative humidity after packaging was tracked at different times. Figure 4-9 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and silver electrode as back electrode (the experimental group uses 4-trifluoromethylsulfonylphenylthiol as the modification layer, and the control group does not contain this modification layer).

[0123] Example 5

[0124] With ZnTiO3 as electron transport layer, FA 0.95 Cs 0.05 PbI3 is the perovskite layer, spiro-OMeTAD is the hole transport layer, 5,5,5-trifluoropentane-1-thiol (structure Figure 3-1 (shown) is the preparation, efficiency and stability testing of an upright perovskite solar cell with a modified layer and a copper electrode as the back electrode.

[0125] Preparation method: Conductive glass cleaning, electron transport layer, perovskite layer, hole transport layer, and modification layer preparation are the same as in Example 1. The modification layer is coated with an isopropanol solution of 5,5,5-trifluoropentane-1-thiol (concentration of 3.5 mg / mL) and is spin-coated on the hole transport layer film at a speed of 3000 rpm.

[0126] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-10 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 The current density-voltage curve of the upright solar cell with PbI3 as the perovskite layer, spiro-OMeTAD as the hole transport layer, and copper electrode as the back electrode (the experimental group uses 5,5,5-trifluoropentane-1-thiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 23.92mAcm -2 , the open circuit voltage is 1.086V, the fill factor is 72.42%, the photoelectric conversion efficiency is 18.81%, and the hysteresis coefficient is 6.2%. The reverse sweep short-circuit current of the experimental group is 24.48mA cm -2 , the open circuit voltage is 1.147V, the fill factor is 78.02%, the photoelectric conversion efficiency is 21.90%, and the hysteresis coefficient is 6.8%. Figure 4-9 Show.

[0127] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed at 65°C and 65% relative humidity after packaging was tracked at different times. Figure 4-11 It shows that ZnTiO3 is used as the electron transport layer, FA 0.95 Cs 0.05 Stability test curve of upright solar cell with PbI3 as perovskite layer, spiro-OMeTAD as hole transport layer and copper electrode as back electrode (the experimental group uses 5,5,5-trifluoropentane-1-thiol as the modification layer, and the control group does not contain this modification layer).

[0128] Example 6

[0129] PTAA is used as the hole transport layer, FA 0.95 Cs 0.05 PbI3 is the perovskite layer, PCBM is the electron transport layer, 4-methylphenylthiol (structure Figure 2-1 (shown) is the preparation, efficiency and stability testing of inverted perovskite solar cells with a modified layer and a gold electrode as the back electrode.

[0130] Preparation method: The cleaning of the conductive glass and the perovskite layer were the same as in Example 1. The coating of the PTAA hole transport layer used a 2.5 mg / mL PTAA / toluene solution, which was spin-coated at 4000 rpm and annealed on a 150°C hot plate for 10 minutes. The preparation of the PCBM electron transport layer used a 23 mg / mL PCBM / chlorobenzene solution to spin-coat the perovskite film at 2000 rpm. The coating of the modification layer used an isopropanol solution of 1-methylphenylthiol (concentration of 5 mg / mL) to spin-coat the electron transport layer film at 3000 rpm. The evaporation of the gold electrode used an electron beam evaporator at 6.0×10 -8 The deposition was carried out under vacuum, and the thickness of the gold electrode was 100 nm (evaporation rate ).

[0131] Solar cell performance output test results: The control group of this experiment did not have a modification layer, and the remaining layers were the same as above. The photoelectric conversion efficiency of the experimental group and the control group was compared using a simulated sunlight (AM 1.5G) test system. Figure 4-11 The hole transport layer is PTAA, and the FA 0.95 Cs 0.05 The current density-voltage curve of an inverted solar cell with PbI3 as the perovskite layer, PCBM as the electron transport layer, and a gold electrode as the back electrode (the experimental group uses 4-methylphenylthiol as the modification layer, and the control group does not contain this modification layer). The results are as follows: The reverse sweep short-circuit current of the control group is 24.14 mA cm -2 , the open circuit voltage is 1.063V, the fill factor is 76.70%, the photoelectric conversion efficiency is 19.69%, and the hysteresis coefficient is 7.5%. The reverse sweep short circuit current of the experimental group is 24.54mAcm -2 , the open circuit voltage is 1.190V, the fill factor is 75.32%, the photoelectric conversion efficiency is 22.04%, and the hysteresis coefficient is 1.8%.

[0132] Solar cell stability test results: The control group of this experiment did not have a modification layer, and the other layers were the same as above. The photoelectric conversion efficiency of the control group and the experimental group placed at 65°C and 65% relative humidity after packaging was tracked at different times. Figure 4-13 The hole transport layer is PTAA, and the FA 0.95 Cs 0.05 Stability test curve of inverted solar cells with PbI3 as perovskite layer, PCBM as electron transport layer and gold electrode as back electrode (the experimental group uses 4-methylphenylthiol as the modification layer, and the control group does not contain this modification layer).

[0133] Comparative Example 1

[0134] A perovskite solar cell was prepared using 3-trifluoromethylpyridine-6-thiol as a modification layer. The preparation process was the same as in Example 1, except that the modification layer was coated using an isopropanol solution of 3-trifluoromethylpyridine-6-thiol (concentration of 5 mg / mL) and was spin-coated on the hole transport layer film at a speed of 3000 rpm.

[0135] The reverse short-circuit current of the battery is 24.62mAcm -2 , the open circuit voltage is 1.155V, the fill factor is 80.52%, the photoelectric conversion efficiency is 22.90%, and the hysteresis coefficient is 4.7%.

[0136] The stability test results of the solar cell:

[0137] After aging for 600 hours in a nitrogen environment at 60°C for an unpackaged device, the device efficiency was measured to be 90% of the initial efficiency.

[0138] Comparative Example 2

[0139] A perovskite solar cell was prepared using 3-trifluoromethylsulfonylpyridine-6-thiol as a modification layer. The preparation process was the same as in Example 2, except that the modification layer was coated using an isopropanol solution of 3-trifluoromethylsulfonylpyridine-6-thiol (concentration of 5 mg / mL) and was spin-coated on the hole transport layer film at a speed of 3000 rpm.

[0140] The reverse short-circuit current of the battery is 24.65mAcm -2 , the open circuit voltage is 1.132V, the fill factor is 77.46%, and the photoelectric conversion efficiency is 21.61%.

[0141] The stability test results of the solar cell:

[0142] After aging for 1000 hours in an environment of 85°C and 85% relative humidity, the device efficiency measured after packaging was 90% of the initial efficiency.

[0143] The above examples confirm that the present invention uses phenylthiol or alkylthiol as a modified layer, which can regulate the Fermi level and oxidation potential of metal electrodes (including a variety of metals commonly used in electrode materials, gold, silver, copper), so that it can be applied to a variety of perovskite solar cells, while being committed to reducing the preparation cost of the device and improving the stability of the device. Moreover, compared to other thiol compounds such as pyridinethiol (which only works on the Fermi level regulation of the copper electrode), the phenylthiol and alkylthiol of the present application can not only work on the Fermi level regulation of the copper electrode, but also effectively regulate the Fermi level of the gold and silver electrodes, so that they can be applied to solar cells with inverted structures. The modified gold electrode is used in an inverted device to achieve a more outstanding photoelectric conversion efficiency of more than 22%, and achieves ultra-high stability (such as Example 6) with almost no attenuation of efficiency after aging for one month. The commonly used back electrodes of inverted perovskite solar cells are silver and copper electrodes. Since the gold electrode itself has higher conductivity and corrosion resistance than silver and copper, adjusting the Fermi level of the gold electrode and applying it to inverted devices has great application prospects and advantages.

[0144] In particular, even when using a normal device with a copper electrode as an example, the efficiency of the device modified with phenylthiol is higher than that of the device with a pyridinethiol compound as the modified layer, which is mainly reflected in slightly higher fill factor and open circuit voltage, and slightly higher photoelectric conversion efficiency. The reason is that compared with the copper Fermi level (-5.06 eV) modified with pyridinethiol (3-trifluoromethylpyridine-6-thiol), the copper electrode modified with 4-trifluoromethylphenylthiol has a Fermi level (-5.08 eV) that is more compatible with the valence band of spiro-OMeTAD (see Examples 1 and Figure 2-1 ).

[0145] In addition, the copper electrode upright device modified by phenylthiol has better stability than the copper electrode upright device modified by pyridinethiol, which may be because the nitrogen atom on the pyridine ring in pyridinethiol tends to exchange protons with the A-site ions in the perovskite, such as the formamidinium cation, thereby destroying the perovskite structure. For example, in the stability comparison between Example 1 and Comparative Example 1, it can be seen that the encapsulated device of Example 1 is placed in a nitrogen environment at 60°C for aging. After 600 hours, the device efficiency still maintains 97% of the initial efficiency. After the device in Comparative Example 1 is placed in the same environment for aging for 600 hours, the device efficiency is 90% of the initial efficiency.

[0146] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements can be made to the present application, all of which fall within the scope of protection of the present application.

Claims

1. A perovskite solar cell, comprising: Metal electrode layer, Modification layer, The first carrier transport layer, Perovskite layer, a second carrier transport layer, and Conductive substrate, Wherein, the constituent material of the modification layer is selected from substituted or unsubstituted phenylthiol compounds, substituted or unsubstituted alkylthiol compounds and combinations thereof.

2. The perovskite solar cell according to claim 1, wherein: The substituted or unsubstituted phenylthiol compound has a structural formula of Formula I, Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

3. The perovskite solar cell according to claim 2, wherein: The substituted or unsubstituted phenylthiol compound has a structural formula of Formula I-1, Among them, R 1 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 11 , where R 11 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl.

4. The perovskite solar cell according to claim 2, wherein: R 1 Independently selected from H, F, methyl, trifluoromethyl, -SO2CF3.

5. The perovskite solar cell according to claim 1, wherein: The substituted or unsubstituted alkylthiol compound has a structural formula of Formula II, Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl; R 3 and R 4 is independently selected at each occurrence from H, halogen, C1-C6 alkyl and C1-C6 haloalkyl; n is 1-5.

6. The perovskite solar cell according to claim 5, wherein: The substituted or unsubstituted alkylthiol compound has the structural formula II-1, Among them, R 2 independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl and -SO2R 21 , where R 21 Independently selected from H, halogen, C1-C6 alkyl, C1-C6 haloalkyl; n is 1-5.

7. The perovskite solar cell according to claim 5, wherein: R 2 Independently selected from H, F, methyl, trifluoromethyl, -SO2CF3.

8. The perovskite solar cell according to claim 1, wherein: The first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer.

9. The perovskite solar cell according to claim 1, wherein: The first carrier transport layer is an electron transport layer, and the second carrier transport layer is a hole transport layer.

10. The perovskite solar cell according to claim 8 or 9, wherein: The hole transport layer comprises a p-type inorganic or organic semiconductor material, preferably selected from NiO x , CuI, CuSCN, spiro-OMeTAD, P3HT, PTAA and combinations thereof.

11. The perovskite solar cell according to claim 8 or 9, wherein: The constituent material of the electron transport layer includes n-type inorganic or organic semiconductor materials, preferably selected from PCBM, ZnTiO3, TiO2, SnO2, ZnO, ZnO-ZnS and combinations thereof.

12. The perovskite solar cell according to claim 8 or 9, wherein: The thickness of the electron transport layer is 10-120 nm; the thickness of the hole transport layer is 50-300 nm.

13. The perovskite solar cell according to claim 1, wherein: The metal electrode layer is selected from gold, silver, copper, aluminum and alloys thereof.

14. The perovskite solar cell according to claim 1, wherein: The perovskite layer comprises AMX3, wherein A is selected from C4H 11 N + 、CH3NH3 + 、HC(NH2)2 + , Cs + and Rb + and combinations thereof; M is selected from Pb 2+ and Sn 2+ and combinations thereof; X is selected from halogen ions and quasi-halogen ions and combinations thereof.

15. The perovskite solar cell according to claim 14, wherein: The thickness of the perovskite layer is 100-800 nm.

16. The perovskite solar cell according to claim 1, wherein: The thickness of the modified layer is 2-5 nm.